CURRENT STATE, INSTITUTIONAL FOUNDATIONS AND DEVELOPMENT PROSPECTS OF ATTRACTING FOREIGN INVESTMENT TO THE REGION - Kenjayev , Ikrom Ergashboyevich (THE INNOVATION ECONOMY, 2026)
The article analyzes the investment policy pursued in Uzbekistan in recent еars and the dynamics of foreign investment inflows by region. It is noted that against the background of global economic changes, high rates of investment activity in the regions, especially in Bukhara, Navoi, Kashkadarya and Tashkent regions. Using the example of Namangan region, a significant increase in the share of foreign investment in 2010-2024, the economic efficiency of modernization projects and structural changes in industries have been studied.